2013
DOI: 10.1165/rcmb.2013-0159rc
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Long Noncoding RNA, SCAL1, Induced by Cigarette Smoke and Elevated in Lung Cancer Cell Lines

Abstract: The incidence of lung diseases and cancer caused by cigarette smoke is increasing. The molecular mechanisms of gene regulation induced by cigarette smoke that ultimately lead to cancer remain unclear. This report describes a novel long noncoding RNA (lncRNA) that is induced by cigarette smoke extract (CSE) both in vitro and in vivo and is elevated in numerous lung cancer cell lines. We have termed this lncRNA the smoke and cancer-associated lncRNA-1 (SCAL1). This lncRNA is located in chromosome 5, and initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
179
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(183 citation statements)
references
References 47 publications
4
179
0
Order By: Relevance
“…Recent studies have indicated that the type and number of lncRNAs vary greatly among species, tissues and cells [7][8][9] , and these macromolecules are biologically functional and associated with the development, progression and treatment response of various diseases, including cancer [10] . Previous studies have shown that MALAT1 [11] , HOTAIR, H19 [12] , the lncRNA GAS6-AS1 [13] and SCAL1 [14] are associated with the development and progression of lung cancer. However, the functional mechanism of lncRNAs remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that the type and number of lncRNAs vary greatly among species, tissues and cells [7][8][9] , and these macromolecules are biologically functional and associated with the development, progression and treatment response of various diseases, including cancer [10] . Previous studies have shown that MALAT1 [11] , HOTAIR, H19 [12] , the lncRNA GAS6-AS1 [13] and SCAL1 [14] are associated with the development and progression of lung cancer. However, the functional mechanism of lncRNAs remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also build upon the recent finding of signaling pathway activation by an external stimulus such as oxidative stress and cigarette smoke, thereby altering lncRNA expression. For example, smoke and cancer-associated lncRNA-1 56 was recently shown to act downstream of nuclear factor erythroid 2-related factor (NRF2) and mediate oxidative stress in lung cancer. Similarly we also observed an NRF2 motif upstream of onco-lncRNA-3, which was found to have elevated expression in KEAP1 mutant patients in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…The 111 LCALs include a lncRNA known to play a role in lung cancer (SCAL1 [16]), cancer-associated lncRNAs not previously implicated in lung cancer (CCAT1 [29], ESC-CAL-1 [30], LINC00261 [31], linc-UBC1 [32], UCA1 [33], ENST00000547963 [34], and PART-1 [35]), a lncRNA implicated in a lethal lung developmental disorder (FENDRR [36]), and three previously unannotated lncRNAs. Interestingly, the remaining 99 lncRNAs were previously annotated in normal human tissues but not implicated in human disease.…”
Section: Characterization Of Novel Lncrnasmentioning
confidence: 99%
“…The most well-characterized lncRNA reported in lung cancer is MALAT1 (metastasis-associated lung adenocarcinoma transcript 1), which is associated with high metastatic potential and poor patient prognosis in non-small cell lung cancer patients with and without metastatic tumors [9,13]. More recent studies have found that the intronic non-coding RNA (ncRNA) lncRNA-LET plays a role in the regulation of hypoxia-mediated metastasis in squamous cell lung carcinoma [14], intronic ncRNA AK126698 confers resistance to cisplatin by targeting the Wnt pathway [15], and the lncRNA SCAL1 (smoke and cancer-associated lncRNA-1) is associated with tobacco-induced lung cancer [16]. These individual studies demonstrate the growing importance of lncRNAs in lung cancer while highlighting the need to systematically identify lncRNAs altered in lung cancer.…”
Section: Introductionmentioning
confidence: 99%